2016
DOI: 10.18632/oncotarget.7702
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of IRE1α-driven pro-survival pathways is a promising therapeutic application in acute myeloid leukemia

Abstract: Survival of cancer cells relies on the unfolded protein response (UPR) to resist stress triggered by the accumulation of misfolded proteins within the endoplasmic reticulum (ER). The IRE1α-XBP1 pathway, a key branch of the UPR, is activated in many cancers. Here, we show that the expression of both mature and spliced forms of XBP1 (XBP1s) is up-regulated in acute myeloid leukemia (AML) cell lines and AML patient samples. IRE1α RNase inhibitors [MKC-3946, 2-hydroxy-1-naphthaldehyde (HNA), STF-083010 and toyocam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 85 publications
2
71
2
Order By: Relevance
“…6G). However, viability of these mutants, especially the highly TKI-resistant FLT3-ITD-D835Y/F mutants 41 , 16 was significantly reduced by both PU-WS13 and ganetespib (Fig. 6G).…”
Section: Hsp90 Protects Flt3-itd-expressing Cells Against Ros and Permentioning
confidence: 98%
“…6G). However, viability of these mutants, especially the highly TKI-resistant FLT3-ITD-D835Y/F mutants 41 , 16 was significantly reduced by both PU-WS13 and ganetespib (Fig. 6G).…”
Section: Hsp90 Protects Flt3-itd-expressing Cells Against Ros and Permentioning
confidence: 98%
“…Accumulating evidence links IRE1 signaling with various aspects of cancer biology. For instance, combination of an IRE1 RNase inhibitor with either bortezomib (a proteasome inhibitor) or arsenic trioxide (AS 2 O 3 ) precluded XBP1 mRNA splicing and alleviated acute myeloid leukemia cell growth (48). The IRE1/XBP1 axis has been also implicated in decreased sensitivity of transformed cells to hypoxia-induced death (49).…”
Section: Ire1mentioning
confidence: 99%
“…11,30,31 In AML, the mean expression of XBP1 is significantly higher in AML patients compared to normal human CD34+ hematopoietic stem and progenitor cells (HSPCs) and this increased expression is associated with hypomethylation of the XBP1 promoter. 32 Several studies have also observed that markers of activated UPR signaling, such as the presence of the XBP1s splice variant and increased expression of UPR-activated genes GRP78 (encoded by HSPA5) , PDI and CALR, are detectable in a significant number of AML patient samples. 3335 However, the regulators of the UPR and the functional consequences of altered UPR signaling in AML have not been defined.…”
Section: Introductionmentioning
confidence: 99%